Latino/a children's and young adult writers on the art of storytelling - Aldama, Frederick Luis, 1969- (Latino and Latin American profiles., 2018)
"This book is an original collection of more than thirty interviews led by Frederick Luis Aldama with Latino/a authors working in the genre."